Inhibitory effects of a novel chrysin-derivative, CPD 6, on acute and chronic skin inflammation - Yu, Chan Hee; Suh, Beomseon; Shin, Iljin; Kim, Eun Hye; Kim, Donghyun; Shin, Young Jun; Chang, Sun Young; Baek, Seung Hoon; Kim, Hyoungsu; Bae, Ok Nam (International Journal of Molecular Sciences, 2019)
The skin is an important physiological barrier against external stimuli, such as ultraviolet radiation (UV), xenobiotics, and bacteria. Dermal inflammatory reactions are associated with various skin disorders, including chemical-induced irritation and atopic dermatitis. Modulation of skin inflammatory response is a therapeutic strategy for skin diseases. Here, we synthesized chrysin-derivatives and identified the most potent derivative of Compound 6 (CPD 6). We evaluated its anti-inflammatory effects in vitro cells of macrophages and keratinocytes, and in vivo dermatitis mouse models. In murine macrophages stimulated by lipopolysaccharide (LPS), CPD 6 significantly attenuated the release of inflammatory mediators such as nitric oxide (NO) (IC50 for NO inhibition: 3.613 μM) and other cytokines. In cultured human keratinocytes, CPD 6 significantly attenuated the release of inflammatory cytokines induced by the combination of IFN-γ and TNF-α, UV irradiation, or chemical irritant stimulation. CPD 6 inhibited NFκB and JAK2/STAT1 signaling pathways, and activated Nrf2/HO-1 signaling. In vivo relevancy of anti-inflammatory effects of CPD 6 was observed in acute and chronic skin inflammation models in mice. CPD 6 showed significant anti-inflammatory properties both in vitro cells and in vivo dermatitis animal models, mediated by the inhibition of the NFκB and JAK2-STAT1 pathways and activation of Nrf2/HO-1 signaling. We propose that the novel chrysin-derivative CPD 6 may be a potential therapeutic agent for skin inflammation.
Keywords: Animals; Anti-Inflammatory Agents; Cytokines; Dermatitis; Dermatologic Agents; Flavonoids; Heme Oxygenase-1; Humans; Janus Kinase 2; Keratinocytes; Macrophages; Male; Mice; Mice, Inbred BALB C; Mice, Inbred ICR; NF-E2-Related Factor 2; NF-kappa B; Nitric Oxide; RAW 264.7 Cells; STAT1 Transcription Factor; Chrysin; Chrysin derivatives; Nrf2/HO-1 signaling; Skin inflammation; Synthetic flavonoid